LANGUAGE IN COURTROOM DISCOURSE - Susanto SUSANTO (Bandar Lampung University (UBL), 2016)
Courtroom discourse, which is in the field of Forensic Linguistics, presents the analysis on legal language used in the courtroom settings (Coulthard & Johnson, 2007; Olsson, 2004; Wang, 2012). It mainly focuses on the legal language as object, process and instrument (Stygall, 1994); and the legal language in enabling and reporting contexts (Matthiessen, 2009). In the paper, I present an overview of some critical issues concerning with the studies of courtroom language. By taking a case study of a Chinese criminal trial, I exemplify some language aspects used in the courtroom to shed light on the nature of the courtroom discourse - the primary speaking roles of a judge in directing, ruling and instructing. Further, I explore the distribution of information in the judge’s speech realized by the tone groups.